Comparative efficacy of non-electric cooling techniques to reduce nutrient solution temperature for the sustainable cultivation of summer vegetables in open-air hydroponics - Nisar, Muhammad Mohsin; Mahmood, Rashid; Tayyab, Salman; Anees, Moazzam; Nadeem, Faisal; Bibi, Sadia; Waseem, Faiza; Ahmed, Nazir; Li, Jing; Song, Zhao (Frontiers in Plant Science, 2024)
The cultivation of summer vegetables in open-air nutrient film technique (NFT) hydroponics is limited due to the elevated nutrient solution temperature (NST). In this regard, non-electric evaporative cooling techniques were explored to maintain NST in open-air NFT hydroponics. Four cooling setups were employed by wrapping Polyvinyl Chloride (PVC) grow pipes with one and two layers of either wet or dry jute fabrics and attaching them with coiled aluminum pipe buried inside a) wet sand-filled brick tunnels (Cooling setup-I) b) two inverted and vertically stacked earthen pots (Cooling setup-II), c) two inverted and vertically stacked earthen pots externally wrapped with wet jute fabric (Wrapped Cooling setup-II) and d) an earthen pitcher wrapped with wet jute fabric (Cooling setup-III). Wrapping grow pipes with two layers of wet jute fabric reduced NST by 5℃ as compared to exposed (naked) grow pipes. The double layer jute fabric wrapped grow pipes produced 182% more reduction in NST in comparison to single layer wrapped grow pipes. Additionally, the installation of Wrapped Cooling setup-II and Cooling setup-III outperformed Cooling setup-I and Cooling setup-II through NST reduction of about 4℃ in comparison to control. Interestingly, the Cooling setup-III showed its effectiveness through NST reductions of 193%, 88% and 23% during 11 am-12 pm as compared to Cooling setup-I, Cooling setup-II and Wrapped Cooling setup-II, respectively. Whereas, the Wrapped Cooling setup-II caused NST reductions of 168%, 191% and 18% during 2-3pm in comparison to Cooling setup-I, Cooling setup-II and Cooling setup-III, respectively. Thus, the double layer jute fabric wrapped grow pipes linked with Wrapped Cooling setup-II can ensure summer vegetables cultivation in open air NFT hydroponics as indicated by the survival of 5 out of 12 vegetables plants till harvest by maintaining NST between 26-28℃.